Water Fraction Ratio of the Sacroiliac Joint Subchondral Bone Marrow in Patients with Ankylosing Spondylitis Predicts the Degree of Disease Activity - Beum Jin Kim; Young Han Lee; Joohee Lee; Sungjun Kim; Ho-Taek Song (Diagnostics, 2022)
Objectives: Ankylosing spondylitis (AS) is a chronic inflammatory arthritis with characteristic involvement of the spine and sacroiliac joints. MRI may be the only indicator of disease activity or response. This study aimed to use a novel water fraction measurement technique on MRI as a biomarker to predict disease activity in patients with AS. Methods: We enrolled 39 patients (18 men [mean age, 38.6 years; range, 18–59 years] and 21 women [mean age, 39.3 years; range, 23–61 years]) who were clinically diagnosed with AS and underwent MRI, including mDixon sequences. Water fraction values of sacroiliac joint subchondral bone marrow were derived from the mDixon sequences. The Ankylosing Spondylitis Disease Activity Score (ASDAS) was recorded using clinical information and laboratory values from medical records. Multiple linear regression, Firth logistic regression, and intraclass correlation coefficients were used for the statistical analysis. Results: In multiple linear regression, water fraction, subchondral bone marrow edema, subchondral bone erosion, and subchondral bone marrow enhancements were significantly associated with ASDAS with C-reactive protein (ASDAS-CRP). The water fraction parameters showed a good linear correlation with ASDAS-CRP and ASDAS with erythrocyte sedimentation rate (ASDAS-ESR) (beta coefficient = 1.98, p < 0.001 and beta coefficient = 1.60, p = 0.003). Firth logistic regression showed that water fraction was a significant predictor of ASDAS-CRP but not ASDAS-ESR. The intraclass correlation coefficient showed excellent repeatability for the three repeated measures of the water fraction. Conclusion: Water fraction parameter could be a good imaging biomarker of disease activity status. The sacroiliac joint evaluated by mDixon MRI may be a promising biomarker of disease progression in patients with spondyloarthritis.